2003
DOI: 10.4269/ajtmh.2003.69.663
|View full text |Cite
|
Sign up to set email alerts
|

A Large Outbreak of Histoplasmosis Among American Travelers Associated With a Hotel in Acapulco, Mexico, Spring 2001

Abstract: During spring 2001, college students from Pennsylvania reported an acute febrile respiratory illness after returning from spring break vacation in Acapulco, Mexico. Acute pulmonary histoplasmosis was presumptively diagnosed and the cluster of illness was reported to the Centers of Disease Control and Prevention. A large investigation then ensued, which included finding student-travelers for interviews and requesting sera for histoplasmosis testing. We defined a clinical case by fever and at least one of the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 8 publications
0
26
0
2
Order By: Relevance
“…Because H. capsulatum is found in soil contaminated with bird or bat droppings, farmers, bird handlers, wood cutters, and speleologists are at risk of contracting histoplasmosis [2][3][4][5]. Activities that disrupt the soil during excavation and the construction, demolition, and rehabilitation of buildings generate infected dust; therefore, construction workers in endemic areas should also be considered to be at a high risk of contracting histoplasmosis [6]. For example, researchers reported a cluster of cases of acute histoplasmosis associated with exposure to soil during a golf course renovation [7].…”
Section: Professions Associated With Ifis Secondary To Inhalation Of mentioning
confidence: 98%
“…Because H. capsulatum is found in soil contaminated with bird or bat droppings, farmers, bird handlers, wood cutters, and speleologists are at risk of contracting histoplasmosis [2][3][4][5]. Activities that disrupt the soil during excavation and the construction, demolition, and rehabilitation of buildings generate infected dust; therefore, construction workers in endemic areas should also be considered to be at a high risk of contracting histoplasmosis [6]. For example, researchers reported a cluster of cases of acute histoplasmosis associated with exposure to soil during a golf course renovation [7].…”
Section: Professions Associated With Ifis Secondary To Inhalation Of mentioning
confidence: 98%
“…Often there is a group history of participation in activities that involve heavy exposure to bat or bird droppings, mostly spelunkers 18,19 or volunteers with recent involvement in cleaning tasks or rehabilitation of old buildings, 20 but one large outbreak in travelers returning from Mexico was reported in which the source of infection was a hotel where all the cases had resided during their trip. 5 In our series, there were no groups, making the diagnosis more challenging, but 8 of the 23 cases formed 4 pairs of travel partners. This difference may simply reflect different travel habits, but may also reflect a higher index of suspicion for histoplasmosis in our setting-a specialist clinic for returning travelers and tropical disease whose staff are more likely to consider histoplasmosis even in isolated cases, as opposed to larger groups of returning travelers with a similar clinical syndrome, in whom the diagnosis may be more apparent.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, other sources of outbreaks may occur as observed with one large outbreak in which the source of infection was apparently a hotel in Acapulco, Mexico. 5 A survey of Spanish travelers returning from Central and South America found that 20% had a positive histoplasmin skin test (versus none of a control group with no history of travel to endemic countries), but only 19% of these had any symptoms. 6 Prolonged travel, sleeping outdoors, and travel to Central (rather than South) America were associated with infection.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in a large outbreak of APH in American travelers vacationing in Acapulco, Mexico, in 2001, 25% of symptomatic, laboratory-confirmed cases received antifungal treatment and 56% received other antimicrobials. 10 Reporting ''sentinel'' cases on ProMED-mail can alert other physicians to possible outbreaks of pulmonary histoplasmosis, facilitating diagnosis and management.…”
Section: Discussionmentioning
confidence: 99%